2005
DOI: 10.1007/s11274-005-9037-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxygen on the sporulation, δ-endotoxin synthesis and toxicity of Bacillus thuringiensis H14

Abstract: The sporulation and toxicity of Bacillus thuringiensis H14 were studied as a function of aeration. The fed-batch cultures carried out in the similar aeration conditions were followed in four different oxygen transfer rates containing 0, 20, 100 and 250 mmol/l/h. The percentage of total cells which had formed refractile spores in these four oxygen transfer rates were 100, 93, 84 and 48%, respectively. The highest rate of sporulation was observed in the absence of oxygen and the mature spores were the only popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…The highest DO concentration (100%) had a strong negative impact on spore production, but toxic activity increased by four times in comparison with values reached with lower DO levels (5%, 20%, or 50%) during phases III and IV (Table 2). These results are in agreement with the reports given by Sarrafzadeh and Navarro (2006), who found lower spore counts and higher toxicity when the sporulation phase of Bti cultures were carried out under saturated oxygen condition. The authors also report that in such a situation mature spores and vegetative cells were the only two populations present at the end of culture, meaning that immature spores were completely absent, a finding also observed here.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The highest DO concentration (100%) had a strong negative impact on spore production, but toxic activity increased by four times in comparison with values reached with lower DO levels (5%, 20%, or 50%) during phases III and IV (Table 2). These results are in agreement with the reports given by Sarrafzadeh and Navarro (2006), who found lower spore counts and higher toxicity when the sporulation phase of Bti cultures were carried out under saturated oxygen condition. The authors also report that in such a situation mature spores and vegetative cells were the only two populations present at the end of culture, meaning that immature spores were completely absent, a finding also observed here.…”
Section: Discussionsupporting
confidence: 93%
“…By applying an identical approach, Avignone-Rossa et al (1992) obtained spore counts similar to those reached in non-limited cultures; however, toxin production was not thoroughly suppressed. Sarrafzadeh and Navarro (2006) found that the interruption of air supply in the course of the fermentation led to a total sporulation of the culture and slightly lower toxicity than that observed in non-limiting conditions. However, the aeration was interrupted after 24 h of fed-batch cultures performed without oxygen limitation, when a considerable portion (40%) of the population had already started sporulation.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…may be induced by the absence of oxygen [28][29][30]. However, cultures of this bacterium under anoxic conditions will halt biomass formation and affect negatively TGase production, as it has been demonstrated by one experiment run by us at 400 rpm and 0 vvm air (0% dissolved oxygen concentration, results not shown).…”
Section: Resultsmentioning
confidence: 78%
“…The toxicity (due to δ-endotoxin and endospore) was about four times higher under non-aerated conditions [27]. Sarrafzadeh and Navarro [28] observed the highest concentration of spores being 100% mature under anaerobic conditions for Bt strain H14. Das and Danker [29] showed that anoxic and water stresses favoured production of spores and crystals at an early stage of growth.…”
Section: Discussionmentioning
confidence: 95%